2016
DOI: 10.1177/0271678x16668889
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of tau protein after cerebral ischemia and reperfusion in rats are similar to those occurring in Alzheimer’s disease – Hyperphosphorylation and cleavage of 4- and 3-repeat tau

Abstract: Epidemiological studies have suggested a close relationship between cerebral ischemia and Alzheimer's disease (AD). To clarify the pathological association of tau dynamics in both diseases, we performed comprehensive studies on the posttranslational modification of tau in cerebral ischemia and reperfusion (I/R) in rats. The present study suggests that both 4-repeat and 3-repeat tau isoforms are hyperphosphorylated in cerebral I/R, similar to the case in AD. The generation of a 60-kDa Asp-truncated tau in cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 53 publications
3
65
0
Order By: Relevance
“…Another study showed that the tau protein can inhibit the transport of the amyloid protein precursor in axons and dendrites, which leads to the deposition of the amyloid protein precursor in the body of a neuronal cell [97]. Available studies demonstrate that following ischemia, hyperphosphorylated tau protein predominates in cortical neurons and accompanies apoptosis [17,95,96,98,99]. The above data indicate that neuronal apoptosis after brain damage due to ischemia-reperfusion is directly associated with hyperphosphorylated tau protein.…”
Section: Tau Protein After Brain Ischemiamentioning
confidence: 94%
See 1 more Smart Citation
“…Another study showed that the tau protein can inhibit the transport of the amyloid protein precursor in axons and dendrites, which leads to the deposition of the amyloid protein precursor in the body of a neuronal cell [97]. Available studies demonstrate that following ischemia, hyperphosphorylated tau protein predominates in cortical neurons and accompanies apoptosis [17,95,96,98,99]. The above data indicate that neuronal apoptosis after brain damage due to ischemia-reperfusion is directly associated with hyperphosphorylated tau protein.…”
Section: Tau Protein After Brain Ischemiamentioning
confidence: 94%
“…Intensive staining of tau protein in neurons, astrocytes, microglial cells, and oligodendrocytes after ischemia was observed in both the hippocampus and cortex [64,[88][89][90][91][92][93][94][95][96]. Another study showed that the tau protein can inhibit the transport of the amyloid protein precursor in axons and dendrites, which leads to the deposition of the amyloid protein precursor in the body of a neuronal cell [97].…”
Section: Tau Protein After Brain Ischemiamentioning
confidence: 99%
“…Initial tau protein staining was presented in both neural and glial cells in the hippocampus, cortex and thalamus in both experimental and human brain ischemia [59,[64][65][66][67][68][69][70][71]. Tau protein was also observed in microglia after focal ischemia of the brain in ischemic penumbra [57,71]. The data presented indicate that some neurons show changes in the tau protein after ischemia-reperfusion brain injury [67], which may be related to the main neuropathological stage of ischemic processes in these cells [69].…”
Section: Tau Protein In Post-ischemic Brainmentioning
confidence: 75%
“…Tau protein accumulated in the blood after a ischemia-reperfusion brain episode [78,79] can cross the ischemic blood-brain barrier and tau protein originating from serum can cause a stronger tau protein pathology in the brain parenchyma [80]. Ischemia-reperfusion brain injury with ischemic insufficiency of the blood-brain barrier [7,[81][82][83][84][85] initiates tau protein phosphorylation [53,54,56,57,77], and phosphorylated tau protein may cause damage to the blood-brain barrier, leading to harmful feedback reactions [74]. The permeability of the blood-brain barrier may exacerbate neuropathology through the tau protein from blood in brain damage as a result of ischemia-reperfusion by increasing its level in brain tissue, which suggests that the ischemic-reperfusion episode of the brain may play an important role in the growth of the blood tau protein level [78][79][80].…”
Section: Tau Protein In the Blood After Brain Ischemia And Ischemic Bmentioning
confidence: 99%
“…Interestingly, a straightforward association has been suggested between ischemic events, tau hyper-phosphorylation and the formation of NFT. In this regard, hyper-phosphorylated and truncated tau-forms, resembling those detected in AD, accumulate after a transient cerebral ischemia [113,114]. In humans NFT pathology is detected in TBI, but presenting remarkable differences in terms of temporal and regional affection: in TBI, NFT are concentrated in the superficial layers in the neocortex, whereas in AD they predominate in the deep layers [115,116].…”
Section: P-taumentioning
confidence: 99%